Professional SlickEdit - Hurst John (Wrox, 2007)
Professional SlickEditis the first guide to the award-winning SlickEdit tools, and is technically reviewed by the SlickEdit development team. SlickEdit expert John Hurst shares his years of experience in developing with SlickEdit to teach readers how to maximize the tool's features, and to write and debug code faster than they have before. Additionally, the book includes a CD ROM with an extended trial version of SlickEdit not available anywhere else.